Reconstruction of global surface ocean pCO.sub.2 using region-specific predictors based on a stepwise FFNN regression algorithm - Zhong, Guorong; Li, Xuegang; Song, Jinming; Qu, Baoxiao; Wang, Fan; Wang, Yanjun; Zhang, Bin; Sun, Xiaoxia; Zhang, Wuchang; Wang, Zhenyan; Ma, Jun; Yuan, Huamao; et al. (Biogeosciences, 2022)
Various machine learning methods were attempted in the global mapping of surface ocean partial pressure of CO.sub.2 (pCO.sub.2) to reduce the uncertainty of the global ocean CO.sub.2 sink estimate due to undersampling of pCO.sub.2 . In previous research, the predictors of pCO.sub.2 were usually selected empirically based on theoretic drivers of surface ocean pCO.sub.2, and the same combination of predictors was applied in all areas except where there was a lack of coverage. However, the differences between the drivers of surface ocean pCO.sub.2 in different regions were not considered. In this work, we combined the stepwise regression algorithm and a feed-forward neural network (FFNN) to select predictors of pCO.sub.2 based on the mean absolute error in each of the 11 biogeochemical provinces defined by the self-organizing map (SOM) method. Based on the predictors selected, a monthly global 1.sup." x 1.sup." surface ocean pCO.sub.2 product from January 1992 to August 2019 was constructed. Validation of different combinations of predictors based on the Surface Ocean CO.sub.2 Atlas (SOCAT) dataset version 2020 and independent observations from time series stations was carried out. The prediction of pCO.sub.2 based on region-specific predictors selected by the stepwise FFNN algorithm was more precise than that based on predictors from previous research. Applying the FFNN size-improving algorithm in each province decreased the mean absolute error (MAE) of the global estimate to 11.32 Âµatm and the root mean square error (RMSE) to 17.99 Âµatm. The script file of the stepwise FFNN algorithm and pCO.sub.2 product are distributed through the Institute of Oceanology of the Chinese Academy of Sciences Marine Science Data Center (IOCAS,